Effective management of intramolecular charge transfer to obtain from blue to violet-blue OLEDs based on a couple of phenanthrene isomers. (November 2015) - Ouyang, Xinhua; Li, Xiang-Long; Zhang, Xingye; Islam, Amjad; Ge, Ziyi; Su, Shi-Jian
Abstract: A couple of phenanthrene isomers were designed and synthesized by introducing strong D–π–A structure strategy to manage effectively their intramolecular charge transfer processes for violet-blue emitters. Their physical properties, including UV–vis, photoluminescence, thermal and electrochemistry, were systematically studied. The results were found to be good candidates as emitters for organic light emitting diodes (OLEDs). The devices based on them exhibit deep-blue light emissions with CIE coordinates of (0.15, 0.15) for p-PATPA and violet-blue (0.16, 0.05) for m-PATPA at 100 cd/m 2, respectively. The violet-blue device shows good performance with external quantum efficiency (EQE), current efficiency (CE), and power efficiency (PE) of 2.39%, 0.78 cd/A, and 0.72 lm/W, respectively. Furthermore, at the high luminescence, the device still indicated good performance with relative low efficiency roll-off. Our results here successfully provide an efficient design strategy with strong donor and acceptor for violet-blue emitters. Graphical abstract: A couple of phenanthrene isomers (PATPA) were designed and synthesized by introducing strong D–π–A structure strategy to manage effectively their intramolecular charge transfer (ICT) processes for violet-blue emitters. Highlights: Novel phenanthrene isomers were synthesized and characterized. Management of their intramolecular charge transfer (ICT) processes for violet-blue emitters. The results were found to be good candidates as emitters for organic light emitting diodes (OLEDs). The devices exhibit violet-blue light emissions with CIE coordinates of 0.16, 0.05) for m-PATPA at 100 cd/m 2, respectively. The results provide an efficient design strategy with strong donor (D) and acceptor (A) for violet-blue emitters.